Renovation of MCK to improve community health in pangambatan village, brand district, Karo Sumut regency - Eddy, Firman; Fachrudin, Hilma Tamiami; Pane, Imam Faisal; Fibriasari, Hesti (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Community service activities are one of the TRI DHARMA university’s obligations. On this occasion, it was reported that community service activities needed improvement in the health sector. The location of this activity is in Pangambatan Village, Kecamatan Merek, Kabupaten Karo, Sumatera Utara and this activity is planned to begin in April until September 2019. The problem in the field is to increase the flow of tourists to Kecamatan Merek to make the need for adequate toilet facilities (MCK). Besides that, it was also found that the community's need for clean water and toilets were used daily by the community. The solution offered is to renovate the MCK facilities for the daily needs of the community and in addition to the toilet facilities for tourists who visit to the village. It is hoped that through this activity the problems in the local community can be overcome.